Implementation of Virtual Laboratory as Media in Elementary School Teacher Education Universitas Pasundan - Devi Rahmiati (Universitas Sebelas Maret, 2019)
The aim this research to get an overview are the using of Virtual Laboratory as media learning students of Elementary School Teacher Education at Universitas Pasundan. The use of media in learning is very important to make solution for lecturers to applied basic concept of science in elementary school. This research in the fourth semester of the Academic Year 2019/2020 in Class A amounting to 40 people. The research method is quasi-experimental with analysis data used a paired t test with SPSS version 21.0 for windows. Based on data analysis, the results is thitung = 2,830 > ttabel = 1,686, then H0 rejected and H1 accepted. It can be concluded that there are significant the used virtual laboratory media in basic concept of science subject in Elementary School Teacher Education at Universitas Pasundan. Its means there are different knowledge and abilities of students at the pre test and post test result if learning used virtual laboratory as media learning in basic concept of science subject at elementary school. The use of virtual laboratory as a media in the learning process will be able to improve and provide a better meaning of learning outcomes characterized students.